1998
DOI: 10.1103/physrevb.57.9050
|View full text |Cite
|
Sign up to set email alerts
|

Excited states and energy relaxation in stacked InAs/GaAs quantum dots

Abstract: Excited states and energy relaxation processes are studied for stacked InAs/GaAs QD's with GaAs cap layers grown by migration enhanced epitaxy. Photoluminescence excitation ͑PLE͒ spectra reveal the excited state spectrum as a function of size for self-assembled InAs QD's in multilayered samples with 36-ML spacers. The observed energy shifts and splittings are consistent with those of hole states numerically calculated for pyramidal QD's supporting assignment to the transition between the electron ground ͉000͘ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
120
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 243 publications
(137 citation statements)
references
References 53 publications
(99 reference statements)
13
120
1
3
Order By: Relevance
“…10 In the present work we observe clear phonon suppression in n-type quasi 0D dots ͑i.e., Landau quantized rather than spatially quantized͒ by a time-resolved intraband absorption measurement. This provides unambiguous evidence for the phonon bottleneck effect independently of arguments concerning which processes dominate in the interband photoluminescence measurements in dots [3][4][5][6][9][10][11][12] and quasi dots 13 such as electron-hole scattering. Further, because of the very clean model system ͑much sharper interfaces and no wetting layer, etc.͒, the interpretation is not complicated by detailed questions about different growth techniques and the quality of different dot sample structures.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…10 In the present work we observe clear phonon suppression in n-type quasi 0D dots ͑i.e., Landau quantized rather than spatially quantized͒ by a time-resolved intraband absorption measurement. This provides unambiguous evidence for the phonon bottleneck effect independently of arguments concerning which processes dominate in the interband photoluminescence measurements in dots [3][4][5][6][9][10][11][12] and quasi dots 13 such as electron-hole scattering. Further, because of the very clean model system ͑much sharper interfaces and no wetting layer, etc.͒, the interpretation is not complicated by detailed questions about different growth techniques and the quality of different dot sample structures.…”
mentioning
confidence: 89%
“…[2][3][4][5][6] However, partly as a result of different groups using different growth techniques for interband photoluminescence samples and partly on fundamental grounds, this is controversial and is the subject of much debate. [7][8][9][10][11][12] Indeed several mechanisms have been proposed that may bypass the bottleneck, such as multiphonon scattering, 7 Auger processes, 8 excitonic effects, 9 and defect related processes. 10 In the present work we observe clear phonon suppression in n-type quasi 0D dots ͑i.e., Landau quantized rather than spatially quantized͒ by a time-resolved intraband absorption measurement.…”
mentioning
confidence: 99%
“…These timescales are determined by generation and diffusion of carriers from the GaAs barrier layers into the QDs, simultaneous state-filling of QD energy levels, and subsequent energy-dependent exciton recombination. Importantly however, it is observed that an increasing optical pump power leads firstly to saturation of the dot ground state (GS) and subsequently of the higher energy states due to comparatively low degeneracy of the GS [24]. Photoluminescence recombination measurements www.lpr-journal.org indicate a shorter recombination time from the excited states (ES) as compared to the GS.…”
Section: Qd Structuresmentioning
confidence: 99%
“…As in Ref. 22 , we suppose uncoupled states arise from QD lateral size variations within the vertical stack. Coupled states, due to their lower ground state, are rst populated.…”
Section: Resultsmentioning
confidence: 99%